ANALISIS KESALAHAN BERBAHASA DALAM KARANGAN NARASI PADA SISWA KELAS V SDN MARGACINTA KECAMATAN SUMEDANG SELATAN - Anggi Citra Apriliana (JMIE (Journal of Madrasah Ibtidaiyah Education), 2019)
This study aims to describe language errors (phonological, morphological, syntactic, semantic, and spelling errors) in narrative essays in class V students of SDN Margacinta, South Sumedang District. To achieve these objectives a descriptive qualitative study was carried out with steps: collecting student language error data and analyzing language errors. The research subjects were fifth grade students of Margacinta Elementary School in South Sumedang District, Sumedang Regency. The results of the study showed that there were language errors in students' narrative essays which included errors in the fields of phonology, morphology, syntax, semantics, and spelling. Phonological errors were 23 (26.74%), morphological errors were 7 (8.13%), syntactic errors were 16 (18.60%), semantic errors were 13 (15.11%), and spelling errors were 27 ( 31.39%). The most common error in the narrative essay is that the spelling error was 27 (31.39%) while the least common type of error was errors in the morphology field of 7 (8.13%) errors. Spelling mistakes that often appear are errors in capital letters, mistakes in writing prepositions, errors in the use of punctuation, and errors in writing words that are not in accordance with the rules of the correct language.